The Role of Sharia Economics in Realizing Sustainable Development in Indonesia - Judijanto, Loso; Nurwanto, Novi (Westscience Press, 2024)
This study provides a comprehensive bibliometric analysis of the role of Sharia economics in promoting sustainable development in Indonesia. By examining 810 publications between 2006 and 2024, the study explores key research trends, themes, and collaborations in the literature. The analysis reveals a significant increase in research activity after 2020, with a focus on aligning Islamic finance principles with sustainable development goals (SDGs), particularly in areas such as poverty alleviation, economic growth, and green finance. Keyword co-occurrence visualizations highlight the importance of concepts such as